Elevated Expression of lncRNA MEG3 Induces Endothelial Dysfunction on HUVECs of IVF Born Offspring via Epigenetic Regulation - Jiang, Ying; Zhu, Hong; Chen, Hong; Yu, Yi-Chen; Xu, Ye-Tao; Liu, Fang; He, Sai-Nan; Sagnelli, Matthew; Zhu, Yi-Min; Luo, Qiong (Frontiers in Cardiovascular Medicine, 2022)
The cardiovascular dysfunction in children born after in vitro fertilization (IVF) has been of great concern, the potential molecular mechanisms for such long-term outcomes are still unknown. Here, we found that systolic blood pressure was a little higher in IVF born offspring at 2 years-old compared to those born by natural conceived. Besides, the expression level of MEG3 was higher in human umbilical vein endothelial cells (HUVECs) of IVF offspring than that in spontaneously born offspring. Pearson correlation test showed that MEG3 relative expression significantly related with the children’s blood pressure (Coefficient=0.429, P=0.0262). Furthermore, we found decreased expression of eNOS and VEGF along with elevated expression of ET1 in HUVECs from IVF offspring, accompanied by lower secretion of nitrite, VEGF, and higher secretion of ET1 in the umbilical cord serum of IVF offspring. Correlation analysis showed MEG3 expression highly correlated with ET1 and Nitrate concentration. With pyrosequencing technology, we found that elevated expression of MEG3 was the result of hypomethylation of the MEG3 promoter. Therefore, our results provide a potential mechanism addressing high-risk of hypertension in IVF offspring via MEG3 epigenetic regulation.